Mapping Plant Biotechnology Research for Low Heavy Metal Accumulation and Crop Safety: A Bibliometric–SLR Study Highlighting CRISPR-Cas9 - Nur Meili Zakiyah; Bella Rhea Lavifa Sanjaya; Sutini Sutini (Universitas Islam Raden Rahmat, Malang, 2026)
Heavy metal contamination in agriculture presents a growing risk to food security, underscoring the need for precise and scalable biotechnological solutions. This study maps the research landscape of plant biotechnology for reducing heavy metal accumulation using an integrated bibliometric analysis (Bibliometrix/Biblioshiny and VOSviewer) combined with a PRISMA-based SLR of 43 English-language empirical articles published between 1997 and 2025. The analysis identifies four major thematic clusters: tolerance mechanisms, field applications, multi-omics, and genome editing that indicating a shift from early physiological studies toward precision biotechnology. The focused SLR reveals that CRISPR-Cas9, although still limited in publication volume, has emerged as a strategically positioned research front, particularly in recent crop-focused genome-editing studies involving agriculturally relevant species. Geographical patterns show strong research productivity in Asia and high scientific influence in Western countries. Despite the modest dataset, this study provides a strategic roadmap for prioritizing CRISPR applications, strengthening interdisciplinary integration, and accelerating biotechnology-based solutions for food safety and sustainable agriculture.